1995
DOI: 10.1021/j100011a002
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation Spectrum of Naphthalene Dimer Cation

Abstract: The electronic spectrum of (CloH8)2+ is obtained in the 455-1400 nm region by applying photodissociation spectroscopy to the ion produced by the laser-induced plasma technique. The spectrum shows a local excitation band at 580 nm and a charge resonance band at 1180 nm. The locations of these bands coincide with those reported for intramolecular dimer cations of dinaphthylpropanes with a partially overlapped conformation, suggesting that (ClOHg)2+ has a similar conformation in the gas phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 3 publications
5
61
1
Order By: Relevance
“…The blueshift of the aromatic CH stretches upon the ionization gives an interesting suggestion for the interpretation of the IR spectrum of the (benzene) 3 ϩ cluster cation, which was reported by Inokuchi et al 9 The (benzene) 3 ϩ cation has the triple sandwich structure with the dimer ion core. Inokuchi et al found a strong IR absorption band at 2986 cm Ϫ1 , and they attributed it to the CH stretch in the dimer ion core.…”
Section: B Benzene-armentioning
confidence: 64%
“…The blueshift of the aromatic CH stretches upon the ionization gives an interesting suggestion for the interpretation of the IR spectrum of the (benzene) 3 ϩ cluster cation, which was reported by Inokuchi et al 9 The (benzene) 3 ϩ cation has the triple sandwich structure with the dimer ion core. Inokuchi et al found a strong IR absorption band at 2986 cm Ϫ1 , and they attributed it to the CH stretch in the dimer ion core.…”
Section: B Benzene-armentioning
confidence: 64%
“…While the charge resonance stabilized, naphthalene dimer cation is thought to possess a structure with cofacial moieties that partially overlap, 29 the geometry of the naphthalene dimer anion can be totally different, as, for instance, in a nonparallel structure with little orbital overlap. We carried out a cursory ab initio calculation that showed that the binding energy of a neutral T-shaped naphthalene dimer is as large as 70% of that of a cofacial dimer.…”
Section: The Geometry Of the Dimer Anionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36] Charge resonance is well known in several aromatic homogeneous dimer cations, where it is characterized by extra stabilization, unique absorption bands, and a charge distribution in which the excess positive charge is evenly distributed over the two aromatic moieties. [25][26][27][28][29][30][31][32][33][34][35][36] Charge resonance is well known in several aromatic homogeneous dimer cations, where it is characterized by extra stabilization, unique absorption bands, and a charge distribution in which the excess positive charge is evenly distributed over the two aromatic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…An analogous CR band is observed also for (toluene͒ 2 ϩ and ͑naphthalene͒ 2 ϩ . 10,11 For these ions, the principal intermolecular interaction is the CR interaction between the -electrons of the aromatic molecules. As seen in Fig.…”
Section: Introductionmentioning
confidence: 99%